Respon Fisik Dan Psikologi Wanita Dengan Kanker Serviks Yang Telah Mendapat Kemoterapi Di RSUD Dr Moewardi Surakarta - Wardani, Erlinda Kusuma; Ambarwati, Winarsih Nur (Universitas Muhammadiyah Surakarta, 2017)
: Cervical cancer is a gynecological disease that causes the most deaths, especially in developing countries. Chemotheraphy is the major alternative treatment of cervical cancer. Chemotheraphy has an impact in many sector of life. Among others, the physical and psychological impact such as psychosocial stress felt by most of women after cervical cancer diagnosis and during treatment. Purpose of this study is to find a representation related to physical and psycological respons in cervical cancer survivor under the chemotheraphy in RSUD Dr Moewardi Surakarta. The design of this research is a qualitative research. Methods: This research is using a phenomenological approach and purposive sampling technique. The number of participant is 8 women who are diagnosed with cervical cancer stage IIB to IVA and had been on chemotheraphy at least 2 times. The methods of data collection is using depth interviews with structure interview technique, observation, field notes, tape recorders and cameras. The result of the study in physical respons includes nausea and vomit, constipation, alopecia, weight loss, peripheral neuropathy, fatigue, decrease in appetite, skin toxicities (vein becomes dark), pain and taste changes. While, the psycological responses which found include anxiety, striving to normality, negative self-esteem, sadness and resignation. Result: Chemotheraphy has the real effects on patients’s physical and psychological.